Complications after Dynamic Hip Screw Osteosynthesis of Proximal Femoral Fractures at Army Instructional Hospital-Libreville - F. M. Bombah; M. Diawara; B. Y. Ekani; T. Nana; A. Mikiela (Case Reports in Orthopedics)
The DHS system is an effective means of open reduction and internal fixation of proximal femur fractures. Postoperative complications are little described and deserve to be studied for better preventive and curative treatment. We report the observations of five (5) patients who presented postoperative complications specific to the DHS system at army instructional Hospital-Libreville. These described complications are related to deterioration of internal fixation leading to callus, nonunion, or infection. Those found are the cut out phenomenon, avascular necrosis of the femoral head, and the fracture of the DHS system. All these complications required surgical revision without functional repercussions at the last follow-up. Complications of internal fixation by the DHS system can be avoided by rigorous asepsis, adequate indications for surgery, and rigorous surgical techniques. Good management can restore hip function.